Heterochromia iridis in acquired Horner syndrome secondary to spontaneous internal carotid artery dissection - Taetrongchit, Nuttacha; Sinsawad, Pannaluck (Journal of Medicine and Health Sciences, 2021)
The aim of this study is to report a rare case of heterochromia iridis in Acquired incomplete Horner syndrome, secondary to spontaneous ipsilateral internal carotid artery dissection in patients with Ehlers-Danlos syndromes. A 23-year-old man complained of left-sided ptosis for two years, but the exact onset of ptosis was unconfirmed. At presentation, the pupils showed anisocoria, which was more apparent in the dark and mild left upper eyelid ptosis was detected. The slit lamp examination showed heterochromia iridis with iris hypopigmentation in the left eye compared to the right eye. The extraocular motilities were normal. The ice test and fatigability test were also negative. The starch iodine test for anhidrosis evaluation was denied by the patient. Left-sided Congenital Horner syndrome (HS) was suspected, but Acquired HS cannot be ruled out. The MRA of the brain include the neck and MRI vessel were done and severe stenosis along the entire course of left internal carotid artery (ICA) from left ICA dissection (ICAD) was shown to be a causal lesion of HS. After a thorough evaluation, the patient was found to have underlying and undiagnosed Ehlers-Danlos syndromes (EDS).